2022
DOI: 10.1002/ejoc.202200298
|View full text |Cite
|
Sign up to set email alerts
|

Employing Ammonia for Diverse Amination Reactions: Recent Developments of Abundantly Available and Challenging Nitrogen Sources

Abstract: Ammonia is the simplest molecule for the installation of nitrogen atom in organic compounds. It is abundantly available, economic and highly attractive from the point of atom economy for its use in organic synthesis, however, an highly challenging task for accessing the nitrogenous scaffolds through NÀ H activation of ammonia. With the advancement of synthetic procedures, scientific community continually developing excellent reactions employing ammonia as a source of nitrogen for various types of amination rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…Furthermore, the result from Stern‐Volmer quenching experiments revealed that the charge transfer of the excited photocatalyst was a single electron transfer (SET) with the copper salt, rather than the thianthrenium salt (for details, see the supporting information). Based on the above results and prior researches, [10c,14a] a plausible mechanism for this visible‐light‐promoted amination reaction was proposed and depicted in Scheme 3. Firstly, excitation of the photocatalyst Ir(III) generates an excited *Ir(III) species, followed by reductive quenching by Cu(I)‐amino species B , which is derived from the coordination of copper salt and ammonia under basic condition, to form Ir(II) as well as Cu(II)‐amino species C .…”
Section: Figurementioning
confidence: 79%
“…Furthermore, the result from Stern‐Volmer quenching experiments revealed that the charge transfer of the excited photocatalyst was a single electron transfer (SET) with the copper salt, rather than the thianthrenium salt (for details, see the supporting information). Based on the above results and prior researches, [10c,14a] a plausible mechanism for this visible‐light‐promoted amination reaction was proposed and depicted in Scheme 3. Firstly, excitation of the photocatalyst Ir(III) generates an excited *Ir(III) species, followed by reductive quenching by Cu(I)‐amino species B , which is derived from the coordination of copper salt and ammonia under basic condition, to form Ir(II) as well as Cu(II)‐amino species C .…”
Section: Figurementioning
confidence: 79%
“…The main drawback of this transformation is the lack of selectivity to the desired amines. [62] Additionally, this access to primary amines was scarcely reported using homogeneous catalysts. [5c,d] In a pioneering contribution, in 1963, Murakami and Kang described the use of a homogeneous cobalt catalyst in situ generated from CoCl 2 • 6H 2 O and KCN for the reductive amination of α-keto acids and esters with ammonium hydroxide by reaction under 49 bar of H 2 at 40-70 °C for 8 h. The corresponding amino-acid derivatives were obtained in 36-95% yields.…”
Section: Reductive Amination Using Ammonia As a Challenging Taskmentioning
confidence: 99%
“…An even more challenging methodology to prepare selectively primary amines is the reductive amination of aldehydes or primary alcohols with ammonia under reductive or hydrogen borrowing conditions, respectively. The main drawback of this transformation is the lack of selectivity to the desired amines [62] . Additionally, this access to primary amines was scarcely reported using homogeneous catalysts [5c,d] .…”
Section: Reductive Amination Using Ammonia As a Challenging Taskmentioning
confidence: 99%
“…Industrial ammonia (NH 3 ) synthesis plays a vital role in modern society as ammonia is a versatile and fundamental feedstock for the manufacture of chemical fertilizers, polymer materials, insecticides, medicine and so on. [1][2][3] Ammonia is also deemed as a promising fuel and clean energy carrier, whose hydrogen content reaches 17.6 wt%. 4 Currently, industrial ammonia synthesis mainly relies on the century-old Haber-Bosch process, in which N 2 and steam-reformed H 2 are converted to NH 3 at elevated temperature (400-500 °C) and high pressure (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%